(untitled) - World Bank (Vietnam, 1996)
The main objective of the preparation was to compose an environmentally-sound investment project for IDA financing for the coastal zone of the Minh Hai, Soc Trang and Tra Vinh province in the Mekong Delta, Vietnam.
Keywords: Coasts,Wetlands,Đất ngập nước ven biển,Environmental protection; Southern Mekong Delta,Southern Mekong Delta,Phía Nam Đồng bằng sông Cửu Long